Association of the Co-stimulatory Molecules Polymorphisms with CMV Infection in Liver Transplant Recipients - Karimi, M. H. (Avicenna Organ Transplantation Institute, 2011)
Background: Co-stimulatory molecules play a critical role in regulating T-cell function during CMV infection after liver transplantation. Objective: To investigate the relationship between the polymorphisms of the co-stimulatory genes and the susceptibility to CMV infection after liver transplantation. Methods: Single nucleotide polymorphisms (SNPs) in PD-1 gene (PD1.1 A/G, PD1.3 A/G, PD1.9 C/T) ICOS (-693 A/G, 1720 C/T), CTLA-4 gene (318 C/T, 1722 T/C, 1661 A/G, 49 A/G) and CD28 (+17 C/T) were analyzed by PCR-RFLP in 70 liver transplant patients. CMV infection was determined in these patients by antigenemia test. Results: CTLA-4 49G showed significant association with CMV infection (p=0.03, OR=3.82, 95% CI: 0–3.5; p=0.01, OR=004, 95% CI: 0–1.3). G and T alleles in CTLA-4 gene (318 C/T and 1661 A/G) (p=0.03, OR=0, 95% CI: 0–3.5; p=0.01, OR=0.04, 95% CI: 0–1.3) were significantly higher in CMV-infected rejector group. Conclusion: CTLA-4 have significant role in CMV pathogenesis and rejection among CMV-positive liver transplant patients.